Pengumuman Dividen terhadap Harga Saham dan Abnormal Return pada Perusahaan Sektor Barang dan Konsumsi di Bursa Efek Indonesia - Muhammad Husni; Abd Rahman; Yohanis Rura; Syarifuddin Rasyid (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2022)
This study aims to determine the effect of dividend announcements on stock prices and abnormal returns on goods and consumption sector companies listed on the Indonesia Stock Exchange for the period 2019-2021. The type of data used is secondary data. The sampling technique used is purposive sampling. The number of samples used was as many as 31 goods and consumption sector companies that made dividend announcements in the period 2019-2021. The data analysis technique uses a paired sample t-test with an observation period of 6 days, which is 3 days before and 3 days after the dividend announcement. The results showed the probability value of the stock price of 0.811 and the abnormal probability value of the return of 0.412, the value of Asymp. The significance of the > 0.05, means that there can be no significant difference between the average stock price and abnormal returns both before and after the dividend announcement.Keywords : Dividend Announcement, Stock Price, Abnormal Return.